Scientific Literacy-Oriented Problem Based Learning Model on Improving Critical Thinking Skills - Auliya, Faridatul; Muchlis (Thinking Skills and Creativity Journal, 2024)
This research was motivated by the difficulty of the buffer solution material and students' critical thinking skills which were still relatively low. Aim of this research is to analyze the effect of implementing a scientific literacy-oriented PBL model on improving students' critical thinking skills in studying buffer solution material. Quantitative approach used in this research uses pre-experimental methods. The target of this research was 35 high school students. Improving students' critical thinking skills in terms of classical completion and hypothesis testing. The results of the research showed that classical mastery in one class had increased, in the pretest by 0% and in the posttest by 91.42%. Hypothesis testing using the Wilcoxon test obtained a significance value of 0.000 (significance <0.05). This shows that there is a significant difference between the pretest and posttest scores of students' critical thinking skills so it can be concluded that there is an influence of the implementation of the scientific literacy-oriented PBL model on students' critical thinking skills. This research has the implication that teachers can use a scientific literacy-oriented PBL model to improve students' critical thinking, the implementation of which is adapted to the material context.